Clinical, radiographic, microbiological, and immunological outcomes of flapped vs. flapless dental implants: a prospective randomized controlled clinical trial. Issue 9 (18th June 2012) - Tsoukaki, Marina; Kalpidis, Christos D. R.; Sakellari, Dimitra; Tsalikis, Lazaros; Mikrogiorgis, George; Konstantinidis, Antonis
Abstract Objectives The objective of this study was to compare the placement of flapped vs. flapless dental implants utilizing clinical, radiographic, microbiological, and immunological parameters. Material and methods A total of 20 patients received 30 dental implants following a one‐stage protocol. The patients were randomly assigned into two study groups: control group with 15 flapped implants and test group with 15 flapless implants. Follow‐up examinations were carried out after 1, 2, 6, and 12 weeks. Clinical recordings, sulcular fluid sampling, microbiological analysis, and digital subtraction radiography were utilized to compare the two surgical approaches. Results Peri‐implant sulcus depth was significantly greater in flapped implants at both 6 and 12 postsurgical weeks (P < 0.001). Flapped implants showed crestal bone loss (0.29 ± 0.06 mm), whereas no bone resorption was detected around flapless implants. Matrix metalloproteinase‐8 values were higher to a statistically significant level in the control group at 1 (P = 0.003) and 6 weeks (P = 0.007) after placement. In the test group, the presence of Porphyromonas gingivalis was significantly higher at the 2nd postoperative week (P = 0.005), whereas the counts of Tannerella forsythia were significantly elevated at the 1st (P = 0.005), 2nd (P = 0.001), and 12th (P = 0.002) postoperative weeks, possibly indicating an earlier formation and maturation of the peri‐implant sulcus. Patients reported more pain after flapped implant placement. Conclusions Flapless implant placement yielded improved clinical, radiographic, and immunological outcomes compared with flapped implantation. In addition, patients seem to better withstand flapless implant placement.